Numerical simulation of microstructural evolution in laser welding process - Cheah, De Yi (Nanyang Technological University, 2021)
Welding has been an essential process in the manufacturing industries. In recent times, it has been introduced into the direct production industry by the means of laser-aided additive manufacturing LAAM). Welded parts are widely used in many industries such as the automotive and aviation industry. In hese industries, the selection of materials is demanding and often requires a long lifespan and reliability to nsure the safety of the passengers. In addition, these materials were expected to undergo a wide range of emperatures. These could affect its mechanical as well as material properties. This project aims to study he effect of how processing parameters can affect the microstructures features of the processed materials during laser welding. In this study, stainless steel is selected as the experimental material. A coupled CA-FV model of finite element method is carried out on transient thermal and microstructural analysis using Open-source Field Operation And Manipulation (OpenFOAM) and ParaView. In this model, a heat source is used to resembles a laser torch. Heat transfer is first used to simulate the emperature evolution during welding. The result from the transient thermal analysis is then retrieved used as an input for microstructural analysis. The heat transfer and cell automaton ffect based on past literature has been considered. Two separate sets of simulations were carried out by arying different values for parameters – laser power and laser scanning velocity. Comparison and onclusion for thermal analysis and microstructural analysis were made. Results from thermal and icrostructure analysis have shown that the 2D the model was able to provide qualitative agreement and prediction of the simulated microstructure ormation during the welding process. Recommendations for future works such as developing a paralleled 3D model were suggested to further decrease the discrepancies between simulated and xperimental results.